Tubular Linear Switched Reluctance Actuator: Design And Characterization - Yeo,, Chin Kiat (2019)
The linear electromagnetic actuator is receiving significant attention due to recent advances in power electronics and modern control method. Besides that, the manufacturing industry is relying on faster and more accurate positioning system in machine tools to meet the increasing demand for higher machining tolerances. Compare to the pneumatic and hydraulic actuator, the linear electromagnetic actuator has a fast dynamic response, high energy efficiency, and high positioning accuracy. In this thesis, a three-phase tubular linear switched reluctance actuator (LSRA) is proposed for the application in semiconductor fabrication industry. The LSRA with tubular structure seems to be attractive for industrial purposes due to both its closed form and inherently absence of normal force compared to the planar type LSRA. In addition, the tubular LSRA has robust construction, low manufacturing and maintenance cost, good fault tolerance capability and high reliability in the harsh environment make it an attractive alternative to permanent magnet linear actuator. However, the tubular LSRA has a long mover which increases the possibility of the mover to deform during fabrication. So, a new mover design is proposed to overcome the problem by separating the mover into mover shaft, magnetic ring and non-magnetic ring. Subsequently, the proposed mover design allows the travelling distance of the actuator to be modified by adding or removing the rings without changing the shaft. In addition, the design procedures, ranging from design specification and structure determination to optimization of actuator parameters is demonstrated in this thesis. The investigation is achieved through the simulation using the Finite Element Method (FEM) analysis and the performance is evaluated based on the generated thrust force. Then, the tubular LSRA prototype is fabricated according to the optimized design. In order to drive the tubular LSRA, three different high current amplifiers together with the switching algorithm are used to provide the correct switching signal due to this method is simple and straightforward while no extensive knowledge of power electronic converter is required. Next, the force and motion characteristics of the tubular LSRA are evaluated to verify the actuator design and the behaviour of the tubular LSRA is obtained through the open loop experiment. The developed tubular LSRA is capable of generating a maximum static force of 0.65 N which is within the required range needed to be operated in semiconductor fabrication process. Through the open loop reciprocating motion, the dynamic responses of the tubular LSRA are capable of achieving a maximum velocity of 210 mm/s and maximum acceleration of 8 m/s2 which are in the performance range for precision mechanism.